Unna Boot in Venous Ulcer Treatment: Evaluation of 30 patients (Annals of Medical Research, 2021)
Aim: We aim to evaluate the results of the Unna boot practice with this prospective study.
Keywords: Venous Ulcer; Unna Boot; Venous Insufficiency.